Pembangunan Identitas Komunitas Rohani Authentic Love Family - Amos Hosea Parningotan; Latif Ahmad Fauzan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the role of the Authentic Love Family (ALF) community in constructing the identities of its members through inclusive philosophies, meaningful social interactions, and innovative communication strategies. Using a qualitative descriptive approach, the research focuses on understanding how ALF creates an environment that fosters spiritual, emotional, and social growth among young Christians. Data were collected through in-depth interviews, participatory observations, and documentation. The findings reveal that ALF’s core philosophy—